In-depth study on tensile properties and finite element analysis of TiC in-situ formed Ti matrix composites with NbC and ZrC additions - Juan Wang; Zhong Yang; Baiqing Zhou; Haijun Zhang; Li Cui; Yadong Niu; Xiaocheng Rui (Journal of Materials Research and Technology)
This study prepared discontinuous particle-reinforced titanium matrix composites (TMC1 - 4) via induction fusion casting and in-situ autogenous techniques, with 5 wt% ZrC as the matrix reinforcing phase and NbC contents of 0, 3, 6, and 9 wt%. XRD, SEM, TEM, and a universal material testing machine were employed to analyse the microstructure and room-temperature mechanical properties. The results demonstrated that increasing NbC enhanced the matrix microstructure, reducing the grain size from 132.5 μm to 62.3 μm, facilitating the α - β phase transition, decreasing the β-phase transition temperature, and stabilizing the β-phase. Meanwhile, the TiC morphology evolved from fine needles to elongated streaks, dendrites, and irregular thick rods. The composite with 6 wt% NbC exhibited a maximum tensile strength of 1180 MPa and an elongation at break of 4.72%. Fracture characterization revealed a transition from ductile to mixed ductile-brittle fracture with increasing NbC. ANSYS-based finite element analysis elucidated the synergistic effect of NbC and ZrC, validating the experimental data and providing a theoretical foundation for material design by simulating stress and fracture mechanisms, thus promoting the development of high-performance composites.